2020
DOI: 10.1186/s12938-020-00801-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of three-dimensional preoperative planning system for the osteosynthesis of distal humerus fractures

Abstract: Background: To reproduce anatomical reduction and appropriate implant placement/choices during osteosynthesis for elbow fractures, we developed a 3D preoperative planning system. To assess the utility of 3D digital preoperative planning for the osteosynthesis of distal humerus fractures, we evaluated the reproducibility of implant reduction shapes and placements in patients with distal humerus fractures. Methods: Twelve patients with distal humerus fractures who underwent osteosynthesis using 3D preoperative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…3D printed models and computer-assisted navigation also provide a secure way to successfully perform minimally invasive techniques. In our previous studies, we clinically applied the 3D preoperative planning system to the osteosynthesis of distal radius and humerus fractures [ 6 , 7 ]. It was found that 3D preoperative planning reduced postoperative correction loss and optimized implant selections [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…3D printed models and computer-assisted navigation also provide a secure way to successfully perform minimally invasive techniques. In our previous studies, we clinically applied the 3D preoperative planning system to the osteosynthesis of distal radius and humerus fractures [ 6 , 7 ]. It was found that 3D preoperative planning reduced postoperative correction loss and optimized implant selections [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the recent advances in preoperative 3D programs for various procedures in orthopedic surgery [3,26,27], it is necessary to establish a method for comparing 3D models of a preoperative plan to 3D models during surgery. The method developed here has the potential to facilitate the comparison of intraoperative 3D models with 3D images of preoperative planning.…”
Section: Discussionmentioning
confidence: 99%
“…This approach was evaluated using artificial plastic SYNBONE models with fractures and was shown to work on cylindrical fragments but performed poorly at fractures near joints. Yoshii et al (2020) also separated the fragments automatically according to the fracture lines and showed that imaging slices of less than 2 mm are required to reach enough accuracy. A multiple region growing method with an automatic seed-point assignment was used by Lee et al (2014) to separate the fragments.…”
Section: Approach 1: Using 3d Medical Imaging Technologiesmentioning
confidence: 99%
“…distal radius stage (LEXI Co., Ltd. Tokyo, Japan)Yoshii et al, 2017, Yoshii et al, 2019b, Yoshii et al, 2019a, Yoshii et al, 2020, Yoshii et al, 2021, Washington, United States)Moldovan et al (2020) Tibia fractures (n = 1) PSBM (Boudissa et al, France)Boudissa et al, 2018;Boudissa et al, 2021a;…”
mentioning
confidence: 99%